Are oral overuse behaviours associated with painful temporomandibular disorders? A cross‐sectional study in Portuguese university students. (23rd July 2021) - Barbosa, Cláudia; Manso, Maria Conceição; Reis, Tiago; Soares, Tânia; Gavinha, Sandra; Ohrbach, Richard
Abstract: Background: Many different types of oral overuse behaviours occur frequently in adult populations with painful temporomandibular disorders (TMDs). Less is known regarding these behaviours and their associations with TMDs in university students. Objectives: Test the association between frequency of different oral overuse behaviours evaluated by the Oral Behaviour Checklist (OBC) and the severity of painful TMDs. Methods: In this cross‐sectional study, 1381 students from 19 universities in the Oporto District, Portugal, completed the Research Diagnostic Criteria for TMD (RDC/TMD) Personal History Questionnaire and the OBC, and they received an RDC/TMD clinical examination. The OBC sum score (ranging from 0 to 84 points) was classified as normal (0 ≤ 16 points), low overuse (17 ≤ 24) or high overuse (≥25). Painful TMD subtypes (myalgia, arthralgia or combined) were identified. Associations were tested using multivariable binary logistic regression models (α = .05), adjusted for age and sex, and referencing the normal parafunction group. Results: University students with high overuse were more likely to have a painful TMD: myalgia (OR = 1.9, 95% CL: 1.3–3.0); arthralgia (OR = 2.2; 95% CL: 1.4–3.4), combined (OR = 5.0; 95% CL: 3.1–8.1). Students with low overuse were more likely to have only the combined painful TMD (OR = 2.4; 95% CL: 1.4–4.0) but not the individual painful disorders. Of the 21 different behaviours, 13 were reported at least 50% of the time. Conclusions: In this university student sample, oral overuse behaviours are widespread, and their overall extent exhibited a dose‐response relationship with respect to severity of painful TMDs based on pain and chronicity. Only some behaviours were independently associated with painful TMDs, suggesting the value of further OBC instrument development.